Estado de exceção no Direito Penal e Processual Penal brasileiro contemporâneo - Reis Júnior, José Carvalho dos (2019)
The present thesis seeks to achieve a theoretical approximation between the concept of State of exception, as an expression of legal suspension of the norm, and the contemporary criminal and procedural Brazilian reality. For this purpose, we will make a picture of the constitucional criminal system of individual guarantees and liberties, presenting to the reader it’s line of action and the importance of the institutes in the democratic system model. In the following chapter we will reconstruct the concepts of State, Constitucional state, Liberal State of Law, Social State of law until we arrive at the current model, the democratic State governed by the rule of the law, demonstrating to the reader it’s bases and primacy. In the sequence we will trace the historical and philosophical evolution of the State of exception, starting from it’s core, in the Roman "iustitium", addressing here the conceptions formulated by Carl Schmitt and, at the modern time, by Giorgio Agamben. When approaching the state of exception, we will present its modern "branches" and its way of acting, notably the judicial activism, the central point of our study, as well as its differentiation with "decrees of urgency", in the Brazilian case the state of siege and of defense. In the last chapter we will present paradigmatic case studies of manifestation, even if shy, of the State of exception within the Brazilian legal regime, drawing the reader the risks of acceptance of this model, especially in the field of legal security and harmony of the system